2015
DOI: 10.1063/1.4916314
|View full text |Cite
|
Sign up to set email alerts
|

Efficient calculation of integrals in mixed ramp-Gaussian basis sets

Abstract: Algorithms for the efficient calculation of two-electron integrals in the newly developed mixed ramp-Gaussian basis sets are presented, alongside a Fortran90 implementation of these algorithms, RampItUp. These new basis sets have significant potential to (1) give some speed-up (estimated at up to 20% for large molecules in fully optimised code) to general-purpose Hartree-Fock (HF) and density functional theory quantum chemistry calculations, replacing all-Gaussian basis sets, and (2) give very large speed-ups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…ramp-ramp shell-pairs and thus dramatically reduces the complexity of two-electron integrals. [15] In combination with modelling ramp-Gaussian shell pairs as a linear combination of ramps, it has been demonstrated that calculation times of ramp-Gaussian basis sets can be competitive with or slightly faster than similar all-Gaussian basis sets [15] for low-angular momentum basis sets.…”
Section: Basis Sets and Core Chemistrymentioning
confidence: 99%
“…ramp-ramp shell-pairs and thus dramatically reduces the complexity of two-electron integrals. [15] In combination with modelling ramp-Gaussian shell pairs as a linear combination of ramps, it has been demonstrated that calculation times of ramp-Gaussian basis sets can be competitive with or slightly faster than similar all-Gaussian basis sets [15] for low-angular momentum basis sets.…”
Section: Basis Sets and Core Chemistrymentioning
confidence: 99%
“…In analogy, the differentials present in Eq. (13) are rewritten as (16) where ∇ Q is the gradient operator andẐ lm (∇ Q ) are the (real) spherical harmonic gradient operators [111]. Heuristically, they are obtained by taking an explicit expression for Z lm (r) and replacing all Cartesian coordinates with the corresponding differentials.…”
Section: A Generalised Mcmurchie-davidson Schemementioning
confidence: 99%
“…This has allowed to treat large systems of chemical or biological significance containing hundreds of electrons and, at the same time, obtain very accurate results for small systems which are intensively studied spectroscopically. Introduction of general explicitly correlated methods [1][2][3], reliable extrapolation techniques [4][5][6][7][8][9], general coupled cluster theories [10,11], and new or improved one-electron basis sets [12][13][14][15][16][17][18][19][20][21][22] made the so-called spectroscopic accuracy (few cm −1 or less) achievable for many small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The support of the function is chosen as 1 Bohr because this enables two-centre ramp-ramp shell pairs to be avoided in most practical calculations (as bond lengths between non-hydrogen atoms are typically greater than 2 Bohr). This choice dramatically decreases the complexity of the twoelectron integrals and enables calculation times with ramp-Gaussian basis sets to be competitive with all-Gaussian basis sets 53 . In this paper, the degree of the ramp, n, is constrained to be an integer, as this makes two-electron integrals easier and avoids unbound derivatives at r = 1 Bohr.…”
Section: Introductionmentioning
confidence: 99%